Introduction to psychodermatology - Ettappurath N Abdul Latheef; Bishrul N A Hafi (Wolters Kluwer Medknow Publications, 2023)
Psychodermatology is an emerging newer subspecialty of dermatology, which comprises dermatology, psychiatry, and psychology. Eventhough the concept is old this dictum has acquired tremendous importance in recent decades. The mind and body are considered as a single unit instead of mind versus body dualism, and this stresses the need for holistic approach of disease management. Formerly, the biomedical concept of disease was very prevalent, which compared the human body to a machine and the doctor was like a technician doing the repair work of human machine, where the mind was completely neglected. But in this recent concept the mind has very important role in health, disease causation and healing. Skin is a part of neuro-immuno-cutaneous-endocrine system. So any disease affecting skin can affect the mind and vise versa. The psycho physiological conditions are highly stress related and secondary psychiatric comorbidities are very common in dermatological conditions especially on visible part of our.